2012
DOI: 10.1038/npp.2012.78
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics in the Human Brain

Abstract: Many cellular constituents in the human brain permanently exit from the cell cycle during pre-or early postnatal development, but little is known about epigenetic regulation of neuronal and glial epigenomes during maturation and aging, including changes in mood and psychosis spectrum disorders and other cognitive or emotional disease. Here, we summarize the current knowledge base as it pertains to genome organization in the human brain, including the regulation of DNA cytosine methylation and hydroxymethylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 160 publications
(182 reference statements)
2
53
0
1
Order By: Relevance
“…Aging and age-related diseases have been associated with site-specific changes in the genome that are mediated by epigenetic mechanisms (Ben-Avraham et al, 2012;Houston et al, 2013;Ricobaraza et al, 2009). For example, studies have found that patterns of DNA methylation and histone modification change with age (Das and Tyler, 2012;Numata et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Aging and age-related diseases have been associated with site-specific changes in the genome that are mediated by epigenetic mechanisms (Ben-Avraham et al, 2012;Houston et al, 2013;Ricobaraza et al, 2009). For example, studies have found that patterns of DNA methylation and histone modification change with age (Das and Tyler, 2012;Numata et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Caution should also be used in extrapolating findings from pre-clinical settings to patient populations. The technical analyses of epigenetic alterations are still under development and in some instances there has been failure to replicate findings in the field of neuropsychiatric epigenetics (Houston et al, 2013). For example, inconsistent results have been reported regarding hypermethylation of the REELIN gene promoter in brains of patients with schizophrenia (Abdolmaleky et Tochigi et al, 2008).…”
Section: Limitationsmentioning
confidence: 99%
“…Variations in glia to neuron ratio can introduce a high degree of heterogeneity and thus affect reproducibility of epigenetic studies examining cohort-based effects in relatively small samples (Houston et al, 2013).…”
Section: Limitationsmentioning
confidence: 99%
“…Altered DNA methylation has been found during brain development in several neuropsychiatric diseases [37][38][39][40]. MECP2, a well-known epigenetic regulation gene, has been reported to be truncated or aberrantly methylated in Rett syndrome and autism [41,42].…”
Section: Altered Dna Methylation In Asdmentioning
confidence: 99%